CHALLENGES AND SOLUTIONS FOR YOUNG ENTREPRENEURSHIP AND BUSINESS SKILLS - Ochilova Gulnoza Odilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article presents the results of research aimed at developing family business and entrepreneurship, the formation of entrepreneurial skills in parents and their children, entrepreneurship of young people in different families, and the socio-psychological characteristics of business skills. In particular, methodological principles of studying the impact of factors such as family business, psychological gender, entrepreneurship, farming, entrepreneurial motivation, motive, gender relations, role distribution, motives for success on entrepreneurial motivation in youth are analyzed.